Halal Tourism Destination Development Strategy Based on Jambi Local Wisdom Seberang City as a Pioneer of Jambi City Halal Tourism Destinations - Isnaeni, Nurida; Lubis, Paulina; Ridhwan, Ridhwan; Chairiyati, Fauziah (Ridwan Institute, 2024)
This study aims to analyze problems and formulate and strategize in the development of halal tourism destinations rooted in local wisdom in Jambi Seberang City. The research method used is a combination of qualitative and quantitative approaches. The specific methodology applied is the Analytic Network Process (ANP), which is implemented through Super Decision software. ANP was chosen for its ability to set priorities in the context of decision making. The results obtained from this study show that the main issue faced is related to government participation. The priority strategies identified include the formation of synergies between various interested parties, increasing government commitment in supporting the development of halal tourism, developing a structured halal tourism development concept, and improving the quality of human resources. Through this research, it is expected to be a source and basis for planning the development of halal tourism in Jamb, especially in Jambi Kota Seberang.